IMPLEMENTASI PERATURAN DAERAH NOMOR 15 TAHUN 2019 TENTANG DESA WISATA DI DESA SOMONGARI - Affiangit, Tesar; Dewi, Mutiar Fitri (Lembaga Riset dan Pengkajian Strategi Pemerintahan IPDN, 2024)
ABSTRACT. As one of the leading sectors, tourism needs to be developed purposefully in order it can contribute significantly to national and regional income which in the end can improve the society welfare. The current trend is the development of tourist villages which is being carried out in various regions in Indonesia, including Somongari Village, Kaligesing District, Purworejo Regency, Central Java. In this research, researchers describe the implementation of Regional Regulation Number 15 of 2019 concerning Tourism Villages and identify supporting and inhibiting factors and efforts to overcome obstacles to implementation. This research is qualitative research with a descriptive approach. The theory used is the implementation theory from Van Meter & Van Horn (1975). Data was collected through in-depth interviews, observation, and documentation. Once collected, the data was then analysed using the interactive analysis model Miles, Huberman, Saldana (2014). The research results indicate that the policy implementation has been successful, as evidenced by four out of six analyzed dimensions being categorized as good, namely the dimension of the characteristics of the implementing organization, the dimension of communication between related organizations and implementing activities, the dimension of the attitudes of the implementers, and the dimension of the social, economic, and political environmental conditions. This success is supported by the strong commitment among policy implementers, effective communication, and the high awareness of the Somongari Village community regarding the development of the tourist village. The inhibiting factors include the lack of understanding among policy implementers regarding Regional Regulation Number 15 of 2019 on Tourist Villages, the inadequate and incompetent resources of Pokdarwis, the suboptimal management of village funds, and the minimal budget support for the development of supporting facilities. Key words: implementation; policy; development; government; tourist village